2021
DOI: 10.1007/s10055-021-00560-z
|View full text |Cite
|
Sign up to set email alerts
|

MagicChem: a MR system based on needs theory for chemical experiments

Abstract: Real chemical experiments may be dangerous or pollute the environment; meanwhile, the preparation of drugs and reagents is time-consuming. Due to the above-mentioned reasons, few experiments can be actually operated by students, which is not conducive to the chemistry learning and the phenomena principle understanding. Recently, due to the impact of Covid-19, many schools adopt online teaching, which is even more detrimental to students' learning of chemistry. Fortunately, MR(mixed reality) technology provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 60 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…A sensor node is a miniature embedded system integrating multiple sensors and communication devices. In addition to sensing the surrounding environment, a sensor node must perform data fusion and forwarding, but it usually has limited energy storage, communication capability, and computational capacity [21]. Due to the self-organizing nature of wireless sensor networks, each sensor node in the network must have specific sensing, communication, and processing capabilities to collect practical information from changes in the surrounding environment, transmit data to and from neighboring nodes, and process the information.…”
Section: Sensor Network Model Constructionmentioning
confidence: 99%
“…A sensor node is a miniature embedded system integrating multiple sensors and communication devices. In addition to sensing the surrounding environment, a sensor node must perform data fusion and forwarding, but it usually has limited energy storage, communication capability, and computational capacity [21]. Due to the self-organizing nature of wireless sensor networks, each sensor node in the network must have specific sensing, communication, and processing capabilities to collect practical information from changes in the surrounding environment, transmit data to and from neighboring nodes, and process the information.…”
Section: Sensor Network Model Constructionmentioning
confidence: 99%
“…Recently, MHN has been used to guide the design of VR environments for long immersive sessions, such as Mixed Reality (MR) office environments, to ensure that the first three levels of MHN are considered to satisfy human deficient needs [14]. Similarly, another MR system has been developed guided by all levels of the MHN model in order to perform chemical experiments [24]. Regarding performance and motivation, a recent review showed that MHN has made significant contributions in management and organization of employees [25].…”
Section: B Maslow's Hierarchy Of Needs (Mhn)mentioning
confidence: 99%
“…VR has proven to be effective in providing comprehensive training in laboratories. For instance, Pan et al developed a mixed-reality (MR) system called MagicChem to train students on three tasks: reaction of sodium with water, exploring the temperature of the flame, and corrosion of stalactites . A total of 56 students participated in the study and were divided into four groups based on the learning environment.…”
Section: Vr Applications In Chemical Safetymentioning
confidence: 99%
“…For instance, Pan et al developed a mixed-reality (MR) system called MagicChem to train students on three tasks: reaction of sodium with water, exploring the temperature of the flame, and corrosion of stalactites. 50 A total of 56 students participated in the study and were divided into four groups based on the learning environment. Analysis of the system usability, user experience, and learning effect was done based on a questionnaire (objective and subjective).…”
Section: Vr Applications In Chemical Safetymentioning
confidence: 99%
See 1 more Smart Citation